Analysis and Synthesis for Interval Type-2 Fuzzy-Model-Based Systems - Li, Hongyi; Wu, Ligang; Lam, Hak-Keung.; Gao, Yabin; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
This book develops a set of reference methods capable of modeling uncertainties existing in membership functions, and analyzing and synthesizing the interval type-2 fuzzy systems with desired performances. It also provides numerous simulation results for various examples, which fill certain gaps in this area of research and may serve as benchmark solutions for the readers. Interval type-2 T-S fuzzy models provide a convenient and flexible method for analysis and synthesis of complex nonlinear systems with uncertainties.
Introduction -- Stability and Stabilization of CTIT2FMBSs -- Output-feedback Control of CTIT2FMBSs -- Sampled-Data Control of CTIT2FMBSs -- Output Tracking Control of CTIT2FSs -- Switched Output-feedback Control of CTIT2FMBSs -- Filter Design of CTIT2FMBSs -- Fault Detection of CTIT2FMBSs -- Model Reduction of CTIT2FMBSs -- Optimal Control of DTIT2FMBSs -- State-feedback Control of DTIT2FMBSs -- Static Output-feedback Control of DTIT2FMBSs -- Guaranteed Cost Output Tracking Control of DTIT2FMBSs.
Keywords: Computational intelligence; System theory; Control theory; Nonlinear Optics; Control engineering; Computational Intelligence; Systems Theory, Control; Nonlinear Optics; Control and Systems Theory